1965
DOI: 10.1016/s0006-3495(65)86708-x
|View full text |Cite
|
Sign up to set email alerts
|

A New Interpretation of the Dynamic Changes of the Potassium Conductance in the Squid Giant Axon

Abstract: The solutions, n(t), of the differential equation dn/dt = alpha (1 - n) n (4 - 6n + 4n(2) - n(3)) - betan(2) (4 - 6n + 4n(2) - n(3)) in which alpha and beta are instantaneous functions of membrane potential, are shown to fit with good accuracy the time courses of the rise of potassium conductance during depolarizing steps in clamp potential, found experimentally by Hodgkin and Huxley and by Cole and Moore. The equation is derived by analysing the dynamic behaviour of a system consisting of a square array of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Various authors have proposed theories of channel gating that postulate interactions among channels. The theories of Tille (1965); Adam (1960) and Hill & Chen (1971) assume cooperative interactions among channels that form a regular array in the membrane, and Tille has shown that the high order kinetics of the Cole & Moore (1960) hyperpolarization delay could be explained by such a theory. Changeux, Thiery, Tung & Kittel (1967) have presented a theory of cooperativity among membrane-bound enzymes which, if applied to ionic channels, would explain the steep voltage-dependence of activation without requiring a large dipole moment in each channel macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have proposed theories of channel gating that postulate interactions among channels. The theories of Tille (1965); Adam (1960) and Hill & Chen (1971) assume cooperative interactions among channels that form a regular array in the membrane, and Tille has shown that the high order kinetics of the Cole & Moore (1960) hyperpolarization delay could be explained by such a theory. Changeux, Thiery, Tung & Kittel (1967) have presented a theory of cooperativity among membrane-bound enzymes which, if applied to ionic channels, would explain the steep voltage-dependence of activation without requiring a large dipole moment in each channel macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…However, n~ is not at all well described in this way, since it continues to increase slowly over tens of millivolts beyond the range of potentials at which it is steeply dependent on E,~. Perhaps this is another reason for suspecting that there might be a better formulation for those currents with a sigmoid time course of activation; we have not pursued this question, although Tille (1965) has presented an alternative approach which does not use power functions.…”
Section: Voltage Dependence Of Equilibrium Constantmentioning
confidence: 99%
“…Nonlinear differential equations describe the potassium conductance. An example of such a description is given by Tille (1965).…”
mentioning
confidence: 99%